Evolution of protein bound Maillard reaction end-products and free Amadori compounds in low lactose milk in presence of fructosamine oxidase I. (1st December 2016) - Troise, Antonio Dario; Buonanno, Martina; Fiore, Alberto; Monti, Simona Maria; Fogliano, Vincenzo
Highlights: The control of Amadori products formation promotes the tuning of the Maillard reaction. Faox is able to deglycate free amino acids in low lactose milk. The formation of bound Maillard reaction end products is mitigated by Faox. Abstract: Thermal treatments and storage influence milk quality, particularly in low lactose milk as the higher concentration of reducing sugars can lead to the increased formation of the Maillard reaction products (MRPs). The control of the Amadori products (APs) formation is the key step to mitigate the Maillard reaction (MR) in milk. The use of fructosamine oxidases, (Faox) provided promising results. In this paper, the effects of Faox I were evaluated by monitoring the concentration of free and bound MRPs in low lactose milk during shelf life. Results showed that the enzyme reduced the formation of protein-bound MRPs down to 79% after six days at 37 °C. Faox I lowered the glycation of almost all the free amino acids resulting effective on basic and polar amino acids. Data here reported corroborate previous findings on the potentiality of Faox enzymes in controlling the early stage of the MR in foods.